Is Sharing One’s Personal Story of Victimization Preferred? Incarcerated Women’s Perspectives on Group Treatment for Sexual Trauma - Marie E. Karlsson; Melissa J. Zielinski; Ana J. Bridges (Social Sciences)
Treatment preferences are an important part of evidence-based practice and have been shown to affect treatment outcomes. In this two-part study, incarcerated women were asked about their preferences for two versions of a trauma-focused group treatment: one that requires sharing their personal memory of sexual victimization (Sharing Required) and one that does not (Sharing Not Required). Study 1 enrolled 88 non-treatment seeking women who evaluated the treatments based on descriptions of the groups. Study 2 was a partially randomized patient preference trial with 85 treatment-seeking women who either agreed to be randomly assigned to one of the two therapy groups or declined randomization and instead were directly assigned to their preferred therapy. Participants in Study 1 evaluated the Sharing Not Required condition more favorably (p < 0.001, Cohen’s d = 0.39). However, the results were affected by PTSD symptom severity as those above the clinical cutoff for probable PTSD evaluated both group treatments more favorably than those below the cutoff (ps < 0.05, Cohen’s ds ≥ 0.46). Study 2 found no significant difference between the proportion of participants who chose Sharing Required, Sharing Not Required, or had no personal preference, and the results did not differ by PTSD symptom severity (ps ≥ 0.70). Outcomes suggest that a variety of forms of trauma-focused therapy may be acceptable to incarcerated women, including those that involve personal narration of trauma memories and those that do not.